Equilibrium linguistic computation method for fuzzy group decision making - Tarmudi, Zamali; Md. Tap, Abu Osman; Abdullah, Mohd Lazim (Institute Mathematical Sciences, Universiti Putra Malaysia, 2012)
This paper proposes an equilibrium computation method using linguistic variables based on the conflicting bifuzzy sets. The linguistic terms were defined and associated with the triangular fuzzy number as well as the labeling system in the early stages. Then, the negation operator was introduced and the bifuzzy approaches were employed to derive the aggregation equilibrium linguistic judgement for evaluation process.